The role of the ankle plantar flexor muscles in trip recovery during walking: a computational modeling study - Namayeshi, Tayebeh; Haddara, Raneem; Ackland, David; Lee, Peter Vee Sin (Frontiers in Sports and Active Living, 2023)
Background: Reactive lower limb muscle function during walking plays a role in balance, stability and ultimately fall prevention. The objective of this study was to evaluate muscle and joint function used to regain balance after trip-based perturbations during walking.Research question: How are lower limb muscles used to recover from external tripping during walking? Method: The dominant legs of twenty healthy adult participants with similar athletic background were tripped using a split-belt instrumented treadmill. High and medium intensity trips were simulated by deceleration of the dominant leg at initial contact from the speed of 1.1m/s to 0m/s and back to 1.1 m/s in 0.4s and 0.8s, respectively. Lower-limb kinematics, kinetics and muscle forces following perturbations were computed to pre-perturbation values using Statistical Parametric Mapping (SPM) paired t-test.Results: A greater ankle dorsiflexion angle (mean difference: 5.3°), ankle plantar flexion moment (mean difference: 0.6𝑁𝑚 𝑘𝑔 ⁄ ), and gastrocnemius and soleus muscle forces (mean difference 4.27𝑁 𝑘𝑔 ⁄ and 13.56𝑁 𝑘𝑔 ⁄ for GAS and SOL, respectively) were observed post-perturbation step despite the magnitude of the perturbation.Significance: This study concludes that adequate timely response of ankle function during a compensatory step is required for successful recovery after tripping during walking in young healthy adults. Weakness in plantar flexors suggests insufficient ankle moments which ultimately can result in falls. The findings of this paper can be used as a reference for the joint moments and range of motion needed to recover trips in the design of assistive devices. In addition to that, clinicians can use the estimated values of muscle forces and the pattern of muscle activities to design targeted training in fall prevention among elderly.